ESTIMASI DAYA DUKUNG PESISIR DENGAN KESEIMBANGAN MASSA (MASS BALANCE) TERHADAP TAMBAK DI DESA LALANG KECAMATAN MEDANG DERAS KABUPATEN BATUBARA - Suria Masriani Sinaga; Yunasfi Djayus; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Research sites in the Desa Lalang Kecamatan Medang Deras Kabupaten Batubara. This research was conducted from july until august 2015. The purpose of this study was to establish potential of area from the marine shrimp farming with mass balance method at Desa Lalang and estimation the carrying capacity of coastal waters of the pond effluent. The data required for analysis of mass balance models of carrying capacity was based on the total ammonia-nitrogen (NH3-N) concentration in coastal waters. Carrying capacity of coastal waters of Desa Lalang Regency maximum pond area calculation may be developed for marine shrimp farming area of 110.733 hectares, this showed that the concentration of ammonia released by the pond had not an impact on the quality of coastal waters because the existing pond area was new opened an area of 100.032 hectars had not exceeded the carrying capacity of the mass balance. Utilization of the existing pond was exceeded carrying capacity then negative impact to coastal area and marine shrimp farming, so be needed to expand it in this area.Keywords: Carrying capacity, coastal area , marine shrimp farming, mass balance